Research on Management Method,Classification and Correlation of Alarm in Information Communication Network - Yang Wang; Guocai Li; Yakun Xu (Dianxin kexue, 2013)
Abstract:As the standardization,refined and integrated development of information communication network management,communication network monitoring is faced with massive network alarm information that has brought new challenges to the network alarm management.The alarm types system composition based on information communication network alarm management were comed up with,the methods from information communication in terms of the effective control of network alarms were discussed,and also the network equipment alarm logic correlation to the logical level of network equipment alarm correlation was extended,at the same time,the study and application of data mining algorithms in alarm correlation was discussed.Finally,the prospect for the intelligent alarm analysis system was provided.